Research on the Design of Micro-class Teaching Mode for Embedded Oral English Teaching in Senior High School - Zhou, Zhou (Journal of Education and Educational Technologies, 2023)
This paper explores how to use the embedded method to carry out low-level oral makeup teaching in the listening and speaking class for 5-8 minutes. The design of the micro-class teaching mode of embedded oral makeup teaching, which is a class in class, is studied and discussed from the aspects of teaching principles, design principles, class structure, and class plan compilation.